Faktor-Faktor yang Mempengaruhi Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Besi di Desa Sokaraja Tengah Kecamatan Sokaraja Kabupaten Banyumas - Puspitasari, Fida Diyah; Saryono; Ramawati, Dian (Jurusan Keperawatan FIKES UNSOED, 2008)
The primary factor that causes high prevalence anemia is caused by low expecting motherÃ¢â‚¬â„¢s obedience in consumings iron supplement during the pregnancy. Based on household health survei (2007) about expecting mother obedience in consuming iron suplement was 23 %. The aim of this researchÃ‚Â is to find out the factors that influence expecting mother obedience in consumings iron suplement during pregnancy at village Sokaraja Tengah district Sokaraja regency Banyumas.This research is an analysis study. The sample was 42 expecting mothers which was taken by purposive sampling. Data were collected from medical report at posyandu and questioner sheet. The result of this research showed there were no significant connection among the factors such as knowledge, attitude, value and belief, income level, health care facilities, care giver behavior and family participation with expecting motherÃ¢â‚¬â„¢s obedienceÃ‚Â consuming iron supplement but the knowledge level was the significantly.Ã‚Â The obedience only influence by factor that connected with obedience knowledge factor, attitude, value and belief, income level, education level, health care facilities, care giver behavior and family participation as much as 41,3 %, and the other factors 58,7 % was unrevealed. The dominant factor expecting mother obedience consuming iron supplement was attitude one.Keywords: Obedience, expecting mother, iron supplement